Handbook on the History of Mathematics Education - Karp, Alexander (Springer New York Imprint: Springer, 2014)
Part 1. History and Methodology of the Field -- 1.On historiography of teaching and learning mathematics -- 2.The History of Mathematics Education: Developing a Research Methodology -- Part 2.Mathematics Education in Different Epochs and in Different Regions: Antiquity and the Middle Ages -- 3.Mathematics Education in Antiquity -- 4.Mathematics Education in Oriental Antiquity and the Middle Ages -- 5.Teaching the Mathematical Sciences in Islamic Societies, 8th-17th Centuries -- 6.Mathematics Education in the European Middle Ages -- Part 3.Mathematics Education in Different Epochs and in Different Regions: Pre-Modern Period -- 7.Mathematics Education in Europe in the Pre-Modern Period -- 8.Mathematics Education in East Asia in the Pre-modern Period -- 9.Mathematics Education in the Americas in the Pre-Modern Period -- Part 4.Mathematics Education in Different Epochs and in Different Regions: Modern Period -- 10.Secondary School Mathematics Teaching in Italy from the Early Nineteenth Century to the Mid-Twentieth Century -- 11.Mathematics Education in France: 1800-1980 -- 12.Mathematics Education in Germany (Modern Times) -- 13.Mathematics Education in the United Kingdom -- 14.Mathematics Education in Spain and Portugal -- 15.Mathematics Education in Russia -- 16.Mathematics Education in the United States and Canada -- 17.Mathematics Education in Latin America -- 18.Mathematics Education in Modern Asia -- 19.Mathematics Education in Africa -- 20.Mathematics Education in Islamic Countries in the Modern Time: Case Study of Tunisia -- Part 5.History of Teaching Mathematical Subjects in School -- 21.History of Teaching Arithmetic -- 22.Notes for a History of the Teaching of Algebra -- 23.History of Teaching Geometry -- 24.History of Teaching Calculus -- 25.History of Teaching Vocational Mathematics -- 26.Mathematics Teaching Practices -- Part 6.Issues and Processes Across Borders -- 27.History of International Cooperation in Mathematics Education -- 28.History of Tools and Technologies in Mathematics Education -- 29.History of Mathematics Teacher Education
Description based upon print version of record
Keywords: Lehrplan; Lehrerbildung; Fachdidaktik; Mathematikunterricht; Methode; Mathematik